"Part of Their Chemistry": The Reproduction of Neoliberal Governmentality in Principal and Teacher Subjectivities. (9th April 2021) - Duarte, Bryan J.
Abstract : In the voyage to increase student achievement, centralized education agencies apply pressure to school principals and teachers in ways that transform their work. This critical ethnographic study of a historically underperforming public elementary school serving predominantly Latinx/a/o students in Texas utilized poststructural theories of subjectivity to demonstrate how the political system of educational policy governs, in plural and contradictory ways, a principal and her teachers in a school serving marginalized youth. The results expose the ways in which neoliberal power is reproduced through the participants who questioned and subtly resisted the practices that they implemented to improve student achievement. The study has implications for both practitioners and researchers to come together in order to reconcile the difficult subjectivities that participants exhibited while they implemented neoliberal policies.